Sustainable development of Sicily east coast area - Caterina Cirelli; Leonardo Mercatanti; Carmelo Maria Porto (European Regional Science Association (ERSA), 2003)
Sicily has an unusual coastal reality: widespread illegal building, industrial pollution, abandonment, under-valued unique sites with strong natural, tourist, cultural and economic potential. A common topic nowadays is the integrated management of the coastal area for a sustainable development. The aspects to consider are many: administrative, managerial, juridical, political, scientific, planning and so on. These aspects will be important both in the realization of operational interventions for the recovery of degraded areas and of eco-compatible planning. It will be necessary to tie the economic development to the maintenance of the environment according to the recent directives of the European Union that point out - in the principles of sustainable development - the guidelines for community politics. In this paper we will focus on the problems of the eastern Sicilian coastal zone (with particular attention paid to coastal protection and port/harbour management) and the opportunities that marine tourism can offer to local development in general.
Keywords: 330